The Potential Area of Kacang Goat Development Base in North Insana District North Central Timor Regency - Randu, Melkianus Dedimus Same; Tulle, Defrys Ridolof; Suek, Ferdinan Suharjono (Universitas Halu Oleo, 2022)
The development of kacang goats based on the base area will encourage the formation of superior commodities in the North Insana District. This study aims to find out the base village area, relative spread/concentration patterns, and the specialization of the kacang goat development area in the North Insana District of TTU Regency. The study used survey methods and secondary data on the number of kacang goat populations in each village in livestock units (ST). Data were analyzed using Location Quotient (LQ), Localita (Lp), and Specialization (Sp). The results showed that four villages were recommended as kacang goat development base areas in the North Insana District of TTU Regency. Positive localita coefficient values ranging from 0.008-0.081 less than one (α £ 1) and the coefficient of positive specialization of 0.003-0.022 less than one (β £ 1) indicate that the cultivation of kacang goats is not concentrated in certain village areas in North Insana Subdistrict and that farmers in each village do not specifically cultivate kacang goats. The research concludes that kacang goats have the potential to be developed as a regionally superior commodity in the North Insana District, TTU Regency.